Multifunctional wax based conductive and piezoresistive nanocomposites for sensing applications - Brito-Pereira, R. (2021)
Carbon nanotube (CNT) and reduced graphene oxide (rGO) filled wax (W) composites were developed and proven to be suitable for screen-printing and molding techniques, allowing simple manufacturing of conductive and multifunctional materials. A homogeneous filler dispersion is essential to obtain smaller filler clusters within the wax. Low electrical percolation thresholds were obtained for CNT/W and rGO/W composites, near 0.3 and 3 wt% filler content, respectively, with maximum electrical conductivity of 2.5 × 10−4 S/m for both fillers. Further, good filler dispersion and mechanical properties have been obtained for all samples. The composites were evaluated as sensing material with good linearity between force and resistance variation. The piezoresistive sensibility is GF < 11 (5 mm of bending) and PS < 0.17 MPa−1 (50 N of pressure), being suitable for the development of sensing applications. Further, the piezoresistive response is stable under cycling solicitations. Finally, the applicability was demonstrated by developing a screen-printed sensor, allowing to detect bending movements, connected to a mobile device through an electronic system.